Preparation and characterization of hydrophobic PVDF membranes by vapor-induced phase separation and application in vacuum membrane distillation - Fan, H.; Peng, Y.; Li, Z.; Chen, P.; Jiang, Q.; Wang, Shaobin (Springer Netherlands, 2013)
Hydrophobic symmetric flat-sheet membranes of polyvinylidene fluoride (PVDF) for use in vacuum membrane distillation (VMD) were successfully fabricated by the vapour induced phase separation (VIPS) method using the double layer casting process. To avoid the delamination that often occurs in double-layered membranes, the same PVDF polymer was employed in both the upper layer and support layer casting solutions. Solutions with low and high PVDF contents were co-cast as the upper layer and support layer of the membrane that was formed. In the VIPS process, the low PVDF content solution favored the formation of a layer with a porous and hydrophobic surface, whereas the solution with a high PVDF concentration favored the formation of a layer with high mechanical strength. The effect of the vapour induced time on the morphological properties of the membranes was studied. As the vapor-induced time was increased, the cross-section of the membrane changed from an asymmetrical finger-like structure to a symmetrical sponge-like structure, and the surface of the membrane became rough and porous. The membrane subjected to the longer vapour induced time also exhibited a higher permeating flux during the VMD process. The best PVDF membrane fabricated in this study had a mean radial pore size of 0.49 µm, and the rough upper surface produced a static contact angle of 145° with water. During the VMD process with a 3.5 wt.% sodium chloride (NaCl) aqueous solution, the best membrane that was fabricated produced a permeating flux of 22.4 kg m-2 h-1 and an NaCl rejection rate of 99.9%at a feed temperature of 73 °C and a downstream pressure of 31.5 kPa. This performance is comparable to or superior to the performances of most of the flat-sheet PVDF membranes reported in the literature and a polytetrafluoroethylene membrane used in this study.